Catheter-directed intra-arterial thrombolysis in the treatment of acute thrombosis of below-the-knee arteries - Luan, Tran Minh Bao (Radiol Case Rep, 2021)
Selecting treatment options in acute arterial thrombosis of the lower extremity, which threatens limb viability, is still a challenge for vascular surgeons. Early restoration of blood flow is crucial and is conducted by surgical thrombectomies or endovascular procedures, depending on patient condition. Catheter-directed thrombolysis with or without percutaneous mechanical thrombectomy for acute limb ischemia has been widely implemented from the early 1990s. Here, we present 2 cases of acute thrombosis of below-the-knee arteries, where we successfully saved the involved limbs using catheter-directed thrombolysis and thrombus aspiration.